Проблематика Апокаліпсису у творчості канадського письменника Дутласа Коупленда - Заїковська, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The author of the article focuses on the problem of Apocalypse in the novels «Generation X», «Girlfriend in a Coma» and «Life After God» by a Canadian writer Douglas Coupland. The author seeks to examine the social nature of Apocalypse and its relation to the search of national identity reflected in these novels.